Geotechnical engineering handbook - Das, Braja M., 1941- (J. Ross Pub., 2011)
Offers coverage of various techniques, methods, applications, and theories in geotechnical engineering. This book brings together essential information on a number of vital topics, including: evaluating of the engineering properties of soils; fundamental principles of slope stability analysis; and, foundation design.